An assessment of success made in local government empowerment programmes and economic empowerment of youth in Ibadan North Local Government Area of Oyo State (2016)
This study examined an assessment of success made in local government empowerment programmes and economic empowerment of youth. The study adopted descriptive research of the expo-facto type. A sample of 295 participants was randomly selected. Reliable instrument were used to collect data from participants still in business. The data was analysed using descriptive statistics, Pearson product, moment correlation, and multiple regression analysis. The result shows that there was a positive significant relationship between Empowerment Programme and Economic Status. But not with social status. It was also discovered that in reverse empowerment was jointly predicted by economic and social status. But economic status is the only potent predictor of empowerment programme. Among others it was recommended that the federal government should encourage all other non-governmental organisation to also assist in empowering youth in the country.